Terahertz Absorber With Reconfigurable Bandwidth Based on Isotropic Vanadium Dioxide Metasurfaces - Zhengyong Song; Maoliang Wei; Zhisheng Wang; Guoxiong Cai; Yineng Liu; Yuanguo Zhou (IEEE Photonics Journal, 2019)
The design of a broadband tunable absorber is proposed based on a thin vanadium dioxide metasurface, which is composed of a simple array of vanadium dioxide and a bottom gold film. When the conductivity of vanadium dioxide is equal to $\text{2000}\ {Ω ^{ - 1}}{\text{cm}^{ - 1}}$ , simulated absorptance exceeds 90% with 71% bandwidth from 0.47 to 0.99 THz and full width at half maximum is 98% from 0.354 to 1.036 THz with center frequency of 0.695 THz. Simulated results show that absorptance peak can be tuned from 5% to 100% when the conductivity changes continually from $\text{10}\ {Ω ^{ - 1}}{\text{cm}^{ - 1}}$ to $\text{2000}\ {Ω ^{ - 1}}{\text{cm}^{ - 1}}$ . The designed absorber may have useful applications in terahertz spectrum such as energy harvesting, thermal emitter, and sensing.